AB1307 Intra- and interreader reliability of the omeract joint space narrowing score on magnetic resonance imaging and computed tomography in rheumatoid arthritis wrist and metacarpophalangeal joints. (23rd January 2014) - Møller Døhn, U.; Conaghan, P.G.; Eshed, I.; Boonen, A.; Bøyesen, P.; Gandjbakhch, F.; Lillegraven, S.; Bird, P.; Foltz, V.; Peterfy, C.G.; Genant, H.K.; Haavardsholm, E.A.; et al.
Abstract : Background: The OMERACT RA MRI scoring system (RAMRIS) evaluates bone erosions, bone edema, and synovitis. The system is validated and increasingly used as an outcome measure in RA clinical trials. However, joint space narrowing (JSN), reflecting cartilage damage, is an important aspect of the joint damage in RA, and reliable assessment of this could constitute a useful additional outcome measure in RA clinical trials. Objectives: The aim of the present OMERACT initiative was to validate the newly proposed MRI scoring system for JSN [1]. Methods: Fourteen RA patients' and one healthy control's 2nd-5th metacarpophalangeal joints (MCP2-5) and wrist on one hand were assessed for JSN on MRI and CT by three experienced readers. Images were read twice with different identification numbers for blinding. Results: Patient demographics: 71% female, age median 61 years (range 31-78), disease duration 5 (1-20), 71% IgM rheumatoid factor positive, Sharp/van der Heijde X-ray scores: Total 75 (3-106), joint space narrowing 40 (1-70), erosion 27 (2-44)). On both MRI and CT, high intrareader (ICCs ≥0.91) and interreader (ICCs ≥0.89) reliability were found for total assessment of JSN (see table). The agreement was generally lower for MCP joints than the wrist, particularly for CT. Conclusions: High intra- and interreader reliabilty was obtained by three readers assessing JSN on MRI and CT using the OMERACT JSN MRI scoring system. The score may be a useful outcome measure in RA clinical trials. References: Østergaard M, et al.: Development and preliminary validation of a magnetic resonance imaging joint space narrowing score for use in rheumatoid arthritis: potential adjunct to the OMERACT RA MRI scoring system. J.Rheumatol. 2011;38:2045-50. Disclosure of Interest: None Declared